2023
DOI: 10.47446/osmia11.6
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected discovery of a near cryptic Dasypoda species in southern Spain (Hymenoptera: Melittidae)

Abstract: A new species of pantaloon bee, Dasypoda (Heterodasypoda) radchenkoi Ghisbain & Wood sp. nov., is described from both males and females collected in the limestone mountains of south-western Spain. COI barcodes show an important differentiation from D. morotei Quilis, 1928 of approximately 9.6% but the morphological divergence between the two species is extremely low. Dasypoda radchenkoi sp. nov. is the fifth species of Heterodasypoda found in Iberia, further confirming the peninsula as the center of divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The total Iberian fauna is represented by approximately 1,100 species belonging to the six major bee families ( Apidae , Andrenidae , Colletidae , Halictidae , Megachilidae and Melittidae ) with approximately 96 species endemic to the Peninsula (8.7%); these values continue to vary due to ongoing taxonomic revisions which both describe and synonymise taxa, as well as adding new records and exclusions (e.g. Ghisbain et al (2021b) , Cross (2023) , Dorchin (2023) , Wood (2023) , Ghisbain et al (2023a) ). Iberia, therefore, hosts slightly over half of the 2,138 bee species from Europe ( Ghisbain et al 2023b ) and around one third of the approximately 3,500 bee species found in the entire West Palaearctic biogeographical region ( Rasmont et al 2017 and subsequent taxonomic works).…”
Section: Introductionmentioning
confidence: 99%
“…The total Iberian fauna is represented by approximately 1,100 species belonging to the six major bee families ( Apidae , Andrenidae , Colletidae , Halictidae , Megachilidae and Melittidae ) with approximately 96 species endemic to the Peninsula (8.7%); these values continue to vary due to ongoing taxonomic revisions which both describe and synonymise taxa, as well as adding new records and exclusions (e.g. Ghisbain et al (2021b) , Cross (2023) , Dorchin (2023) , Wood (2023) , Ghisbain et al (2023a) ). Iberia, therefore, hosts slightly over half of the 2,138 bee species from Europe ( Ghisbain et al 2023b ) and around one third of the approximately 3,500 bee species found in the entire West Palaearctic biogeographical region ( Rasmont et al 2017 and subsequent taxonomic works).…”
Section: Introductionmentioning
confidence: 99%